The concept of preconditions for industrialization - Nicol, Robert C. (1997)
Although A. Gerschenkron some decades ago argued very convincingly that thepreconditions for a country’s industrialization are not rigid nevertheless it still makes senseto try and identify the preconditions that should be approximately fulfilled in order that acountry may industrialize. This idea is applied to Brazil in the XIXth century. JEL Classification: N66; O25; O14.